Socio – economic Factors Influencing Access to Agricultural Extension Services among Smallholder Farmers in Western Uganda - Midamba, Dick Chune; Muteti, Francisca Ndinda; Mpofu, Taddias Prince; Ouko, Kevin Okoth; Kwesiga, Mary; Ouya, Fredrick Ochieng; Chepkoech, Beatrice (Asian Journal of Agricultural Extension, Economics & Sociology, 2022)
The low agricultural productivity reported in both cash and food crops across Uganda is attributed to inadequate skills on modern agriculture. Consequently, many studies have recommended that farmers should be trained on modern agriculture through extension service provision. Strikingly, majority of the farmers do not have access to extension services, a situation which contributes to low returns on investment in agriculture. The study determined the number of farmers with access to extension services, compared them against their counterparts without access to extension services and finally determined the factors affecting access to agricultural extension services using primary data collected from 200 farmers in western Uganda. Data were analyzed using descriptive statistics, t-test, Chi – square test and Binary logistic regression model. From the results, 42.5% of the farmers had access to extension services, those who had access to extension services reported higher crop yields than their counterparts. The significant factors affecting access to agricultural extension services included age (P<0.05), gender (P<0.05), education (P<0.01), distance to the extension areas (P<0.01), membership to agricultural associations (P<0.10) and access to credit (P<0.05). The policy recommendations include; supporting farmers through quick loans at low interest rates, strengthening and increasing the number of adult literacy programs, increasing the number of extension agents and encouraging farmers to join agricultural associations.
Keywords: Agricultural extension; Binary logit; Low productivity